1999
DOI: 10.1097/00005537-199905000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Expression of protein p27 is associated with progression and prognosis in laryngeal cancer

Abstract: We concluded that assessment of p27 expression is useful as a prognostic factor for laryngeal SCC and of value in selecting patients with laryngeal SCC for aggressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 17 publications
4
22
0
1
Order By: Relevance
“…The percentage of p21-and p27-positive tumor cells was expressed as a ratio of positive cells to the total number of tumor cells counted. In accordance with previous studies (12,15,16), tumors with ≤10% of p21-and p27-positive cells were considered to be negative for p21 and p27 expression, respectively.…”
Section: Immunohistological Stainingmentioning
confidence: 71%
See 1 more Smart Citation
“…The percentage of p21-and p27-positive tumor cells was expressed as a ratio of positive cells to the total number of tumor cells counted. In accordance with previous studies (12,15,16), tumors with ≤10% of p21-and p27-positive cells were considered to be negative for p21 and p27 expression, respectively.…”
Section: Immunohistological Stainingmentioning
confidence: 71%
“…With regard to correlation with apoptosis, recent immunohistological study showed a significant correlation between p27 expression and increased apoptosis in oral and oropharygeal SCC (11). With regard to correlation with clinical outcomes, some reports have indicated a significant correlation between decreased expression levels of p21 or p27 and poorer prognoses in laryngeal SCC (12), but contradictory results were reported (10). Although a significant correlation between higher proliferation activities of tumor cells and poorer prognoses was reported for head and neck SCC except for maxillary SCC (13), no correlation was reported in laryngeal SCC (14).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have investigated the clinico-prognostic role of p27 in LSCCs. Absent p27 expression has been statistically associated with advanced clinical stage, lymph node involvement and distant metastasis [13]. However, Korkmaz et al [32] found that p27 overexpression was a [56] failed to find any statistically significant correlation between p53 expression and disease stage but did find statistically significant associations with histological grades (I, II, and III).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of p27 expression has been considered clinically relevant to HNSCC. In patients with oral and laryngeal cancers, reduced p27 expression has been shown to be correlated with poor prognoses, unfavorable treatment responses and metastases [13,34,50,61].…”
Section: Introductionmentioning
confidence: 99%
“…Positive staining for COX-2 was located mainly in the cytosol, and p27 in the nucleus. Immunocytochemical staining was classified as follows [10] : number of positive cells < 10% was deemed as negative (-), 10%-25% as (+), 25%-50% as (++), and > 50% as (+++). …”
Section: Methodsmentioning
confidence: 99%